TEACHING FOR THE STUDENTS LEXICAL SKILLS OF NON-LINQUISTIC UNIVERSITY - Iskakova, Sh. G.; Shibintayeva, A. A. (Ғылым және білім №3, 2020)
Methods of formation of lexical skills in teaching English language are approved in this article. This article offers different types of tasks for the development of oral and written forms of communication. Special attention is paid to the formation of lexical abilities and skills, as this requires knowledge of situational, social and contextual rules. It was concluded that vocabulary is extremely important aspect of language, and ability of communication in any foreign language depends on level lexical skills development level, control and assessment of proficiency level in a foreign language are the most important component of educational process. The main goals of teaching foreign languages in a non-linguistic university are the formation and improvement of the communicative skills of students in other languages for solving problems of interpersonal and intercultural interaction. В данной статье рассматривается методы формирования лексических умений при обучении английскому языку. В данной статье предлагаются различные виды заданий для развития устной и письменной форм общения. Особое внимание уделяется формированию лексических умений и навыков, так как для этого требуется знание ситуативных, социальных и контекстуальных правил. Cтатья посвящена таким понятиям, как: лексические навыки, структуры и качества лексических навыков, стабильные условия, необходимые для формирования лексических навыков, а также этапы изучения каждой новой лексической еди-ницы. Изучение профессиональной лексики является одним из важнейших компонентов педагогической практики; это основа особого языка, который является наиболее динамичным процессом, если учесть, как быстро появляются новые профессиональные термины и как так быстро уходят из употребления старые.
Keywords: рк; научный журнал; периодическое издание; отечественное издание; языкознание; устная форма общения; письменная форма общения; лексические навыки; competence; foreign language; vocabulary; communicative skills; technology